RESPONS PERTUMBUHAN BIBIT KOPI ARABIKA TERHADAP PEMBERIAN EKSTRAK BAWANG MERAH (Allium cepa L.) - Wijaya, Ryan; Adelina, Enny (Fakultas Pertanian, Universitas Tadulako, 2023)
The objective of this study was to achieve optimal concentrations for promoting the growth of Arabica coffee seedlings. This investigation was carried out in the Screen House at Tadulako University's Faculty of Agriculture in Palu, Central Sulawesi. The research lasted from April until August of 2020. Using a Randomized Block Design (RBD) with a single factor—shallot extract—three treatments were used, each replicated nine times, for a total of 81 experimental units: E1 at 40%, E2 at 50%, and E3 at 60%. An analysis of variance (with a significance level of 5%) was performed to assess the impact of these interventions on the observed parameters. In cases where statistically significant effects were found, a second honest significant difference test (5% BNJ) was performed. The results showed that applying different doses of shallot extract stimulated Arabica coffee seedling growth, as shown by increased plant height, leaf count, and stem diameter. Notably, a 60% shallot extract concentration had a particularly significant influence on the growth rate of Arabica coffee seedlings.